The mined volume calculation in the traditional mining area by using the Unmanned Aerial Vehicle (UAV) approach in the observation area of CV. Sinergi Karya Solutif, Patikraja district, Banyumas regency, East Java province, Indonesia - Sigit Allobunga; Ratih Hardini Kusuma Putri; Muhammad Abdurrozak Siamashari; Ika Justitia Julita; Ahmad Ubaidillah Fathoni; Heru Dwiriawan (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2022)
The studies become performed in Notog Village, Patigkraja District, Banyumas Regency, Central Java Province withinside the statement place of CV. Sinergi Karya Solutif with the purpose of comparing the extent of minerals and describing the way to calculate the extent mined with a greater green approach. In measuring and calculating the volumetric minerals, its miles are executed via way of means of the use of the UAV (Unmanned Aerial Vehicle) approach or drones which include drones to get aerial photos. The gathered records may be the number one records utilized in carrying out volumetric analysis. They have a look at becoming performed for 2 (two) months. The consequences acquired withinside the shape of aerial image records as number one records and a base map inclusive of geography, topography, and geology as assisting records. Mined extent acquired via way of means of processing records the use of assisting software program is 11.568.136 m3 at the same time as in records processing the use of different techniques on this guide is 123,365 m3. From the 2 calculation techniques, its miles recognized that the distinction withinside the mined extent is 768.363 m3.